Modelling the Implications of Covid-19 Pandemic on Healthcare Access in Rural South Africa: Appraising Sustainable Development Goal 3 - Sawada, Loveness; Monama, Sakiel Albert (Department of Public Administration, 2024)
Most studies have concentrated on the impacts of Covid-19 on socio-economic development. Despite this focus, there remains a significant gap in the literature, with limited exploration into how the Covid-19 pandemic has presented substantial challenges in rural South Africa, particularly concerning healthcare access, and how it has hindered progress towards the achievement of sustainable development goal 3 outlined in Agenda 2030. This paper seeks to analyse the consequences of the Covid-19 pandemic, which have created obstacles in the pursuit of the Sustainable Development Goals (SDGs) of Agenda 2030, specifically goal 3, which aims to ensure healthy lives and well-being for all individuals across all age groups. The paper contends that the Covid-19 pandemic has presented formidable hurdles that have impeded healthcare access and advancement in numerous rural communities in South Africa. Currently, many rural regions appear to be falling behind in their efforts to guarantee healthy lives and improve societal well-being, as outlined in SDG 3 of Agenda 2030 and Sections 24 and 27 of the Constitution of the Republic of South Africa (1996). This paper is primarily theoretical, drawing extensively from an examination of existing literature to establish its arguments, supported by a desk-based study that reinforces its position. The paper reveals that the Covid-19 pandemic has affected South Africa’s interim strategy to accomplish SDG 3, which aims to ensure healthy lives and promote well-being for all individuals by 2030, by necessitating a duplication of its budget and a reallocation of resources towards healthcare-related initiatives. In conclusion, the paper asserts that achieving universal good health and well-being (SDG 3) by 2030 is currently unfeasible and speculative for rural South Africa, given the country’s considerable distance to cover and numerous socio-economic challenges that are impeding progress. This paper recommends early strategic planning and innovative approaches from both public and private stakeholders to advance good health and well-being for all, thereby realising the objectives of SDG 3 of Agenda 2030.